The location, hazard assessment and sealing of unsafe mine openings in the Central Witwatersrand Gold Mining Basin - Heath, Gregory John (My University, 2010)
One of the most unfortunate legacies of more than 100 years of mining in the Central Witwatersrand Mining Basin is the presence of many unsafe mine related openings such as shafts and subsidences that are present in the southern part of the city of Johannesburg. Using available mine plans and knowledge of the manner in which these holes were formed, a search was undertaken and a total of 244 openings were located. A literature survey revealed that perimeter walls, concrete seals and plugs have most often been used to prevent human access to these unsafe mine openings. Locally mine openings have most often been backfilled with available materials though concrete plugs or seals, walls and fences have also commonly been used. In order to assess which holes should be considered for sealing, a simple “hole risk rating system” was developed, which considered the depth of the hole and its proximity to settlements or thoroughfares. During a Department of Minerals and Energy project led by the author, it was concluded that concrete plugs were probably the most effective method of sealing such unsafe mine openings. Eighty holes were thus sealed using unreinforced, concrete plugs. Polyurethane Foam (PUF) has been used as an alternative method to seal mine openings in the United States for nearly 25 years and was used here to seal two abandoned mine openings. This method requires minimal design, engineering supervision and offers a quick, simple, cost effective and environmentally friendly method of sealing such openings. The documentation of the mine openings, the openings plugged, the methods of plugging and the locations of the plugged holes ia a valuable practical and historical record. The plugging of many holes is a significant contribution to public safety.